Pengembangan Perangkat Penilaian Unjuk Kerja Tematik pada Pembelajaran Tatap Muka Terbatas di Sekolah Dasar - Harman Harman (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to compile and develop an assessment tool for limited face-to-face learning (PTMT). This research was conducted at SDN 175 Kawarasan, East Luwu Regency using the Research and Development research model by adopting the 4D model developed by Thiagarajan, Semmel, & Semmel (define, design, develop, disseminate) into 3D (define, design, develop). The products developed in the form of grids, student worksheets, teacher observation sheets, and assessment rubrics. Media content validation is carried out by a team of validators, empirical reliability tests are obtained through subject trials. The data analysis technique uses quantitative analysis. The validity uses the Gregory pattern and the reliability of the test results uses agreement between observers using the Cohen's Kappa coefficient. The results of developing a performance assessment tool in thematic learning for class V SDN 175 Kawarasan show a theoretical content validity coefficient of 0.95 l greater than 0.75 and declared valid. The reliability coefficient of 0.980 is greater than 0.75 and the device is reliable.